The Reflection That Connects Us with Ourselves, with the Present, and with our Future Perspectives - Gabriella GORBAI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Hungarians’ history is replete with painful episodes; as a consequence, a certain pessimistic outlook has been embedded into the Hungarian culture. The university is home now to students – future teachers of religion, future pastors – whose parents, grandparents, and great-grandparents lived and worked under the oppressive regime and who (also) for this reason approach the past in a rather negative way. They lived for too long in silent despair, without joy, without sufficient food, in fear of informers who would anonymously give out anybody to the “authorities” in hope of personal advantages and rewards. This generation will probably have a hard time believing that those horrible times can never re-turn. This period is also marked by the fact that these people, in most cases, had mind-numbing, treadmill-like, soul-crushing jobs. In these circumstances, nothing was prompting them to improve their performance, and they sooner or later resigned themselves to only meet the minimal expectations. They were not concerned with the future because they did not hope that with a more purposeful attitude, with more efficient work their lot could be improved. On the other hand, their attitude towards the present had become more and more pessimistic. “Why even try if my life is controlled by forces on which I have no influence whatsoever?” This young generation of teachers/pastors has still heard too often the stories of the painful past and were in many cases eyewitnesses to their parents’ and grandparents’ daily struggles or saw them surrender their future goals and be-come disillusioned with the future. During their training as teachers, the victim experience and pessimistic viewpoint (unconsciously) inherited from their forefathers quite often show up in the students’ decisions, in their reactions to certain professional or life situations, in their conflict management and coping methods. In this paper, we will first show the ideal attitude towards the past, the pre-sent, and the future, based on the theory presented by Philip Zimbardo and John Boyd, which leads to a much more balanced and happy life for individuals as well as at the level of nations. Then we will outline the reflection phase model based on the new insights, with the help of which, in our opinion, the attitude of the students at the Faculty of Reformed Theology towards the past, present, and future can be shaped in a positive direction.